The Influence of Promotion, Brand Image and Facilities on the Decision to Choose Prime One School - Katrine; Edwin Sugesti Nasution (Outline Journal of Education, 2022)
This study aims to determine the Effect of Promotion, Brand Image, and Facilities Toward Decision To Choose Prime One School. The population in this study were all parents of students in Prime One School in 2019 totaling 1.699 people. The sampling technique used in this study was the Slovin formula and amounted to 94 respondents. The results of the analysis of the study showed that the Promotion and Brand Image partially have a positive and significant effect on the decision to choose a Prime One School school while Facility have no effect. The results showed that the Promotion, Brand Image and Facilities simultaneously have a significant effect on The decision to choose Prime One School. The results of this study are supported by the value of Adjusted R Square R2 which means that Promotion, Brand Image and Facilities can explain the decision to choose and the remaining is influenced by other variables outside of this study such as service quality, psychological factors.